Development of TVET Teachers’ Beliefs about Technology Enriched Instruction through Professional Development Workshops: Application of the Technology Acceptance Model - M. Salleh, Sallimah; Musa, Juraidah; Jaidin, Jainatul Halida; Shahrill, Masitah (Journal of Technical Education and Training, 2020)
This study explores how Technical and Vocational Teachers’ intentions to incorporate technology in teaching and learning are influenced by their beliefs. It is theorised that teachers’ beliefs about using technology in their instructions are influenced by teachers’ perceptions of technology usefulness, ease of use, and self-efficacy. In the current study, a series of workshops for technology-enriched instructions were mounted for the professional development of technical and vocational teachers. In these workshops, teachers planned, designed and developed 21st century learning activities. Data was collected using a questionnaire, which was distributed to the TVET teacher participants after the completion of the professional development workshops for technology-enriched instruction. The data was subjected to confirmatory factor analysis, and structural equation modelling which were used to analyze the proposed modified Technology Acceptance Model (TAM) model. The modified TAM model proposed that TVET teachers’ intention to use technology, and their beliefs about self-efficacy are directly influenced by their beliefs about perceived ease of use, and perceived usefulness of technology, and that the variable, self-efficacy is a mediator variable to intention. It was shown that the proposed modified TAM model is a good fit model to explain the variance in 52% of teachers’ beliefs about the self-efficacy, and 40% variance of intention. The positive outcome of the technology enriched instruction professional development program is that it provided a common language and skills that overcame some of the TVET teachers’ concerns with regards to technology integration in their lessons. This study contributes towards an understanding of the factors that influence TVET teachers’ intentions to use technology in teaching and learning through a professional development programme for technology enriched instruction.